2021
DOI: 10.1038/s43247-020-00078-3
|View full text |Cite|
|
Sign up to set email alerts
|

The radius of the umbrella cloud helps characterize large explosive volcanic eruptions

Abstract: Eruption source parameters (in particular erupted volume and column height) are used by volcanologists to inform volcanic hazard assessments and to classify explosive volcanic eruptions. Estimations of source parameters are associated with large uncertainties due to various factors, including complex tephra sedimentation patterns from gravitationally spreading umbrella clouds. We modify an advection-diffusion model to investigate this effect. Using this model, source parameters for the climactic phase of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
3
9
0
Order By: Relevance
“…A VEI 4 volume can be reached if the largest end of the largest estimate (Weibull method) is used with the addition of the base surge deposits. This is more consistent with the VEI classification of Constantinescu et al ( 2021 ) for the observed plume height of 17–21 km (Bachmeier 2020 ; Perttu et al 2020 ) and umbrella radius of 100 km (Lagmay et al 2021 ) of Taal Volcano’s main eruption in 2020.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A VEI 4 volume can be reached if the largest end of the largest estimate (Weibull method) is used with the addition of the base surge deposits. This is more consistent with the VEI classification of Constantinescu et al ( 2021 ) for the observed plume height of 17–21 km (Bachmeier 2020 ; Perttu et al 2020 ) and umbrella radius of 100 km (Lagmay et al 2021 ) of Taal Volcano’s main eruption in 2020.…”
Section: Discussionsupporting
confidence: 89%
“…However, using the probabilistic approach (Weibull method) with 90% confidence interval, the volume estimate can be as high as 0.097 km 3 which is close to the lower end of the volume range of VEI 4 (0.1–1 km 3 ). Adding the volume of the base surge deposits amounting to 0.019 km 3 (Lagmay et al 2021 ), the total erupted volume translates to a VEI of 4, consistent with the classification criteria of Constantinescu et al ( 2021 ), namely (1) volume of ejecta; (2) eruption plume height; and (3) umbrella cloud radius. The total erupted volume was calculated using crowdsourced and field survey data, whereas the erupted height and umbrella cloud radius are direct measurements from satellite data of Taal Volcano’s 2020 main eruption plume (Bachmeier 2020 ; Perttu et al 2020 ; Lagmay et al 2021 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…1 ), which by 8:00 pm reached a height of 17-21 km 1 – 3 with an E-W diameter of ~ 100 km. The eruption height and umbrella diameter suggest that the eruption was characterized by mass discharge rates 31 , 32 in the order of 10 7 kgs −1 equivalent to a Volcanic Explosivity Index (VEI)=4. Intense activity lasted up to about 10 hours and started to wane in the morning of 13 January 2020 at about 2:49 am when lava fountaining was observed 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Fero et al (2009) and Stohl et al (2011) showed that initial source conditions have significant effects on the simulation of volcanic ash transport. Constantinescu et al (2021) proved that an enhanced initial condition provides an overall better fit of the tephra deposit generated from an ash cloud than do models without a disk-like source, demonstrating the significant impact of initial condition on ash dispersion. Besides location of the eruption vent and timing of the release, traditional VATD simulation requires key global descriptors of the volcanic plume, especially plume height, grain size, eruption duration and mass loading, or alternatively, a mass eruption rate (MER).…”
Section: Introductionmentioning
confidence: 95%